Donor and Ring‐Fusing Engineering for Far‐Red to Near‐Infrared Triphenylpyrylium Fluorophores with Enhanced Fluorescence Performance for Sensing and Imaging - Wen, Si‐Yu; Zhang, Wei; Ren, Tian‐Bing; Zhang, Qian‐Ling; Liu, Yu‐Peng; Shi, Ling; Hu, Rongfeng; Zhang, Xiao‐Bing; Yuan, Lin (Chemistry : a European journal, 2019)
Fluorescent probes have become an indispensable tool in the detection and imaging of biological and disease‐related analytes due to their sensitivity and technical simplicity. In particular, fluorescent probes with far‐red to near‐infrared (FR‐NIR) emissions are very attractive for biomedical applications. However, many available FR‐NIR fluorophores suffer from small Stokes shifts and sometimes low quantum yields, resulting in self‐quenching and low contrast. In this work, we describe the rational design and engineering of FR‐NIR 2,4,6‐triphenylpyrylium‐based fluorophores (TPP‐Fluors) with the help of theoretical calculations. Our strategy is based on the appending of electron‐donating substituents and fusing groups onto 2,4,6‐triphenylpyrylium. In contrast to the parent TPP with short emission wavelength, weak quantum yields, and low chemical stability, the obtained novel TPP‐Fluors display some favorable properties, such as long‐wavelength emission, large Stokes shifts, moderate to high quantum yields, and chemical stability. TPP‐Fluors demonstrate their biological value as mitochondria‐specific labeling reagents due to their inherently positive nature. In addition, TPP‐Fluors can also be applied to develop ratiometric fluorescent probes, as the electron‐donating ability of the 2,6‐phenyl substituents is closely correlated with their emission wavelength. A proof‐of‐concept ratiometric probe has been developed by derivatizing the amino groups of TPP‐Fluor for the detection and imaging of nitroreductase in vitro and in hypoxic cells. Rigidified and activated probes: Rational modification of the 2,4,6‐triphenylpyrylium salt (TPP) results in fluorophores (TPPF) with far‐red to NIR emissions, large Stokes shifts, and high quantum yields (see figure). In addition, through acylation of the amino groups, TPPF dye can be exploited as a novel platform for designing ratiometric fluorescent probes with highly shifted emission bands.